Effect of conscious sedation and deep sedation on the vagal response characteristics during ganglionated plexus ablation. (7th July 2021) - Aksu, Tolga; Yalin, Kivanc; John, Leah; Osorio, Jose; Winterfield, Jeffrey; Aras, Dursun; Gopinathannair, Rakesh
Abstract: Introduction: We aimed to determine the effects of conscious and deep sedation on vagal response (VR) characteristics during ganglionated plexus (GP) ablation. Methods: Forty consecutive patients undergoing GP ablation for vasovagal syncope were divided to receive conscious sedation with midazolam (Group 1, n = 29) or deep sedation with the midazolam–propofol combination (Group 2, n = 11). VR was defined on three levels. R–R interval increase of >50% (Level 1); R–R interval increase of 20%–50% (Level 2); and R–R interval increase of <20% (Level 3). Results: The ratio of Level 1 VR during ablation on left superior and inferior GPs was significantly lower in Group 2 ( p < .0001 and p = .034, respectively). Once the cut‐off for VR was decreased to Level 2, the ratio of (+) VR was similar between groups during ablation of left‐sided GPs. Positive VR in any level was lower than 20% during ablation of right‐sided GPs. Conclusions: The autonomic tone might be affected in different ways by the level or type of intravenous sedation. Awareness of anesthesia‐related differences may be important if GP ablation will be performed by using VR characteristics during ablation.